Content Based Image Retrieval Using Lacunarity and Color Moments Of Skin Diseases - I Gusti Ayu Triwayuni; I Ketut Gede Darma Putra; I Putu Agus Eka Pratama (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The research conducted contributed in the form of CBIR application which was developed using texture and color feature extraction in searching the contents information of an object of skin disease image. The textured feature is extracted using Lacunarity, while for color feature extraction using Color Moments as well as a combination of both methods. The results of color characteristic extraction test using Color Moments Method yielded images corresponding to 100% similarity percentages and experimentation of texture characteristic extraction using Lacunarity Method yielded images corresponding to a percentage of suitability of 25%, followed by a combined test of both methods and the normalization process produces images corresponding to a percentage of conformity of 60%.